2022
DOI: 10.1039/d1cp05670k
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight into the destabilization of p53TD tetramer by cancer-related R337H mutation: a molecular dynamics study

Abstract: The p53 protein is a tumor suppressor crucial for cell cycle and genome integrity. In a very large proportion of human cancers, p53 is frequently inactivated by mutations located in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…R337H is the most common mutation in the TD, and it is associated with Li-Fraumeni syndrome, which gives rise to several types of cancer. Due to its correlation with cancer, this mutant has been studied and characterised by several groups [ 55 , 56 , 57 , 58 , 59 ], as well as in yeast [ 15 ] and mouse [ 60 ] models. Di Giammarino and co-workers reported that R337H strongly destabilises the tetramer and that its stability is pH-dependent, i.e., tetramer stability is partially recovered by decreasing the pH to acidic values [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…R337H is the most common mutation in the TD, and it is associated with Li-Fraumeni syndrome, which gives rise to several types of cancer. Due to its correlation with cancer, this mutant has been studied and characterised by several groups [ 55 , 56 , 57 , 58 , 59 ], as well as in yeast [ 15 ] and mouse [ 60 ] models. Di Giammarino and co-workers reported that R337H strongly destabilises the tetramer and that its stability is pH-dependent, i.e., tetramer stability is partially recovered by decreasing the pH to acidic values [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…This method has been widely used to analyze MD trajectories. [66][67][68] The aMD simulations were reweighted using the PyReweighting toolkit 69 to calculate the 2D PMF profiles of PC1 and PC2 in three CD147-CypA systems (Fig. S2b, d and f, ESI †).…”
Section: Dynamic Information Of the Cd147-cypa Complexmentioning
confidence: 99%
“…Moreover, ADH-6 inhibits the aggregation of R248W p53 in human cancer cells, restoring the transcriptional activity of p53, leading to cell cycle arrest and apoptosis. 19 Molecular dynamics (MD) simulations have been extensively employed to investigate the conformational properties of different domains of the p53 protein and its mutants, 41,42,[63][64][65][66][67][68][69] as well as the interactions between p53 protein domains and small molecules, 70 short peptides, 71 and other proteins. [72][73][74][75] In spite of experimental and computational studies, it remains mostly unknown how the R248W mutation induces destabilization of R248W p53C and how ADH-6 stabilizes R248W p53C.…”
Section: Introductionmentioning
confidence: 99%